Psychometric properties of the assessment of quality of working life scale in the urban transport sector - Figueroa-Chaves, Hernán Alberto; Bastidas-Jurado, Claudia Fernanda; Gonzáles-Limas, Wilson Redin; Zambrano-Guerrero, Christian Alexander; Matabanchoy-Tulcan, Sonia Maritza (Universidad y Salud, 2017)
Introduction: The Quality of Working Life (QWL) is the degree of satisfaction, physical, mental and social well-being experienced by people in their working environment; it contains the objective and subjective dimensions. For this study, the subjective dimension of the QWL was addressed, which is formed by occupational health, labor welfare and perception of the work. Objective: To determine the psychometric properties of the assessment of quality of life scale at work in the transport sector. Materials and methods: A quantitative descriptive-instrumental study of the scale was made, which consists of 108 items and was applied to 468 drivers of the strategic system of public transport in the city of San Juan de Pasto. The evidence of Kaiser Meyer Olkin and roundness of Bartlett, the factorial analysis and Cronbach Alpha were calculated. Results: The scale presented appropriate features of validity and reliability. It evaluates two factors: labor welfare and healthy life styles, and the respective scales to be applied are presented. Conclusions: The factorial analysis allows us to affirm that the Scale of Quality of Working Life in the transport sector can be applied in subsequent studies.